1999
DOI: 10.1128/jvi.73.6.4983-4990.1999
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Mediated p21 (WAF1/SDII/CIP1) Gene Transfer Induces Apoptosis of Human Cervical Cancer Cell Lines

Abstract: p21(WAF1/SDII/CIP1) (p21) arrests cell growth by inhibiting cyclin-depend kinases. To explore the potential of using p21 for the gene therapy of cervical cancer, we infected human papillomavirus (HPV)-positive cervical cancer cells (HeLa, SiHa, and Z172) and HPV-negative cervical cancer cells (C33A) with recombinant adenovirus encoding p21 cDNA. The results revealed that effective inhibition of cell growth could be achieved by sense p21 adenovirus but not antisense p21 adenovirus infection and occurred through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Recent studies also suggest that p21 has an apoptotic function. For example, apoptosis was induced by p21 transfection in retinoblastoma cells and HPV-positive cervical cancer cells (21,22). Moreover, another recent study showed that p21 was indispensable for apoptosis induction in MCF-7 breast cancer cells, but not for cell cycle arrest (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also suggest that p21 has an apoptotic function. For example, apoptosis was induced by p21 transfection in retinoblastoma cells and HPV-positive cervical cancer cells (21,22). Moreover, another recent study showed that p21 was indispensable for apoptosis induction in MCF-7 breast cancer cells, but not for cell cycle arrest (45).…”
Section: Discussionmentioning
confidence: 99%
“…Following UV irradiation, p21 induction was firstly demonstrated to be p53 dependent (19). However, after UV irradiation, it was also shown that p21 could be induced by a p53-independent pathway (20) and could have an apoptotic function independent of p53 and pRb (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…( 25,26 ) However, due to differences in the experimental conditions for investigation of the effects, contradictory conclusions have been drawn regarding the relationship between p21 and the induction of apoptosis. ( 27,28 ) In order to investigate the basis for the striking differences in the biological responses to p21 expression, we measured the kinetics of p21 protein increase, as well as its expression levels following Ad‐p21F or ‐N infection by increasing MOI of the viral vector. Whereas 20 MOI Ad‐p21 infection resulted in elongated, growth‐arrested cells showing the morphological features of senescence, cells infected with 40 or 50 MOI Ad‐p21 became rounded, contracted, and lost their ability to adhere to the plate with Apo‐taq‐positive staining (Fig.…”
mentioning
confidence: 99%
“…The discovery of p21 gene has provided not only a lucid access to negative regulation of the cell cycle as an inhibitor of cyclin–Cdk complex, but also a direct link between tumor suppressor protein and the cell cycle because a gene, named WAF1, that had an identical cDNA sequence was identified simultaneously and was induced by wild‐type p53 but not mutant p53 gene expression 2. In addition to cell cycle regulation and tumor suppression mediated by p53, p21 is involved in many other functions including differentiation and apoptosis 7–9. Recently, Albrecht et al reported that p21 expression is regulated by p53‐dependent and ‐independent pathways in the liver and is up‐regulated in a biphasic manner with enhanced mRNA expression during G1‐phase and after S‐phase according to hepatic regeneration after partial hepatectomy 28.…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that p21 protein is a universal inhibitor of cylin/Cdk activity and a mediator of growth arrest caused by p53‐dependent and p53‐independent pathways including the antimitogenic hormone‐transforming growth factor–β (TGF‐β), oxidative stress, irradiation, and terminal differentiation 3–7. p21 protein induces G1 arrest of the cell cycle in which action is essential for differentiation and apoptosis 7–9. Therefore, the cells that lost the activity to express p21 cannot regulate those cell cycles to attain G1 arrest for apoptosis and may lead to unregulated cell proliferation as a step toward carcinogenesis.…”
mentioning
confidence: 99%